Comprehensive Application of Borehole Fine Detection Methods: A Case Study in Shantou Bay Subsea Tunnel - Chengkun Wang; Zhengyu Liu; Zhao Dong; Fengkai Zhang; Chuanyi Ma; Xiaolin Xu; Qian Guo (Geofluids)
Water inrush disaster is one of the most severe problems during the construction of sea tunnels, primarily due to faults, karst, and weathered zones. Once a water inrush disaster occurs, it can lead to construction delays, traffic disruptions, and major economic losses, as well as potential consequences such as seawater intrusion, casualties, project suspension, and tunnel closure. Thus, advanced geological prediction is indispensable. During the construction of the Shantou Bay subsea tunnel, a sudden water inrush accident occurred in the sea–land transition section. To prevent such incidents and ensure safety, an integrated approach was employed. Firstly, the cross-hole resistivity method was used to predict water content in front of the tunnel, as it is highly sensitive to water. Subsequently, borehole ground-penetrating radar was applied to finely characterize the geological structure. By combining these two methods, the size, scale, location, water content, and spatial distribution of water-bearing structures in front of the tunnel were identified. With the above measures, the Shantou Bay subsea tunnel passed through the detection section successfully. Herein, we present a case study and offer a valuable reference for similar projects concerning subsea tunnel construction.